2022
DOI: 10.1111/fcp.12782
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone dexborneol protects cerebral ischemia reperfusion injury through activating Nrf2/HO‐1 signaling pathway in mice

Abstract: Stroke is the leading cause of disability and death. When blood flow is restored after prolonged ischemia and hypoxia, it leads to excessive production of reactive oxygen species (ROS), increased local inflammation, and apoptosis, which are the cause of most cerebral ischemia reperfusion injury (CIRI), leading to secondary brain tissue damage. Edaravone dexborneol is a novel neuroprotective agent consisting of edaravone and borneol. Studies have shown that it has synergistic antioxidant and antiinflammatory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Neuroinflammation is one of the key factors of I/R injury, which has a profound impact on the prognosis of cerebral I/R. It is worth noting that C.EDA can reduce the levels of inflammatory factors and free radicals, and protect neurons in the models of cerebral ischemia and post‐stroke depression (Xu et al, 2022; Yajie Zhang et al, 2022). However, the specific function and anti‐inflammatory mechanism of C.EDA in I/R injury is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation is one of the key factors of I/R injury, which has a profound impact on the prognosis of cerebral I/R. It is worth noting that C.EDA can reduce the levels of inflammatory factors and free radicals, and protect neurons in the models of cerebral ischemia and post‐stroke depression (Xu et al, 2022; Yajie Zhang et al, 2022). However, the specific function and anti‐inflammatory mechanism of C.EDA in I/R injury is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For stroke, it was revealed that Eda.B could scavenge free radicals, decrease infarct area, and inhibit proinflammatory mediator expression in rats [ 14 ]. After 2020, more researches about Eda.B on stroke and subarachnoid hemorrhage were conducted [ 21 , 22 ]. These studies still focused on the anti-inflammatory effects of Eda.B.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that Eda.B could promote M2 macrophage polarization via the JAK2-STAT3 signaling pathway [ 15 ]. A recently published study pointed that Eda.B could stimulate the Nrf2/HO-1 pathway to inhibit NADPH oxidase 2 expression in mice after stroke [ 22 ]. Considering the relative mechanism of NET production, the apoptotic pathways may play an important role in the pharmacological effect of Eda.B.…”
Section: Discussionmentioning
confidence: 99%
“…The American Heart/Stroke Association’s journal Stroke published the results of China’s ED phase III trial online ( Xu et al, 2021 ). It was found that ED can protect hippocampal HT22 neurons, astrocytes, and vascular endothelial cells under stress, indicating that it can protect the entire neurovascular unit and inhibit neural apoptosis ( Lee et al, 2010 ; Chen et al, 2022 ; Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%